2017
DOI: 10.1002/app.45209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and strain rate on the tensile behavior of polypropylene composites insulator coatings used in offshore deepwater pipelines

Abstract: Polypropylene (PP) composites are being increasingly used as thermal insulation coatings in both onshore and offshore pipelines. In this study, the direct tensile behavior of pure PP, PP with glass microsphere filler, and PP with 65% glass filler were investigated at 22, 60, and 90 °C temperatures at various strain rates from 0.003/min to 0.300/min. Fourier transform infrared spectroscopy and scanning electron microscope studies were used to characterize the materials. Stress–strain relationships of the materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The performance of PP can be improved by adding rigid, inorganic fillers such as CaCO3 and glass microspheres [1]. PP and its composites reinforced with glass fiber and glass microsphere have many applications in the automobile, aerospace, appliances, and subsea pipeline insulation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of PP can be improved by adding rigid, inorganic fillers such as CaCO3 and glass microspheres [1]. PP and its composites reinforced with glass fiber and glass microsphere have many applications in the automobile, aerospace, appliances, and subsea pipeline insulation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene (PP) was one of the most widely used polyolefin materials, which had a wide range of applications in the fields of electronic and electrical appliances, automobile manufacturing, protective packaging, and construction. [1][2][3][4][5] Currently, the primary way to prepare flame retardant PP was to load additive-type flame retardants into PP. These flame retardants usually include brominated flame retardant, 6 intumescent flame retardant (IFR), [7][8][9][10] and metal hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Shokrieh and Moshrefzadeh-Sani 5 obtained the stress–strain curve of the whole damage process of composites through simulation using an incremental algorithm method, calculated the axial stiffness and strength of each layer by introducing the shear lag theory of Halpin–Tsai, and calculated the residual strength of the damaged layers by introducing the Tsai–Wu failure criterion. Vipulanandan and Guezo 6 studied the direct tensile behavior of polypropylene (PP) composite materials under different temperatures; on the basis of experimental results, constitutive models that incorporate strain rate and temperature were developed for predicting the yield strength, initial elastic modulus, and secant modulus at yield of the PP composites. Nazari and colleagues 7 presented an analytical model for predicting the fracture toughness of composites and concluded that this property of composites increases with an upward fracture toughness gradient of a propagating crack and vice versa.…”
Section: Introductionmentioning
confidence: 99%